Development of Yam-Starch-Based Bioplastics with the Addition of Chitosan and Clove Oil - Ulyarti, Ulyarti; Lavlinesia, Lavlinesia; Surhaini, Surhaini; Siregar, Nurainun; Tomara, Anggel; Lisani, Lisani; Nazarudin, Nazarudin (UI Scholars Hub, 2021)
The potency of yam starch (Dioscorea alata) as film-forming material together with the potency of chitosan and clove oil as antibacterial materials has led the authors to produce active bioplastics based on these materials. This research was performed to determine the effect of chitosan and clove oil on the physical, mechanical, and barrier properties of yam starch’s active bioplastics. The best bioplastics produced were further tested for their antimicrobiological properties. This study used a completely randomized design with five levels of chitosan concentration (1%, 1.2%, 1.4%, 1.6%, and 1.8%) and five levels of clove oil concentration (0.3%, 0.6%, 0.9%, 1.2%, and 1.5%). Each treatment was repeated four times. The results showed that the concentrations of chitosan and clove oil had a significant effect on the thickness and water vapor transmission rate of film but did not affect its solubility and compressive strength much. The use of 1% chitosan or 1.5% clove oil produced biofilms with the lowest water vapor transmission rate. Both plastics also exhibited strong antibacterial activity against Staphylococcus aureus with chitosan bioplastics having a larger inhibition zone than that of clove oil bioplastics.